A survey on the influence of developer emotions on software coding productivity. (29th October 2020) - Anany, Mohammed R.; Hussein, Heba M.W.; Aly, Sherif G.
In this paper, we survey the major research efforts found in literature to develop an understanding of human emotions in relation to its effect on software coding productivity. To achieve this, we first highlight the main contributions for eliciting user emotions, including their properties, representation, limitations, and available APIs. We then report on our survey of the important factors that influence software coding productivity and various metrics to measure it. We aim to focus on productivity aspects measured over short durations of time, and not only measuring effort consumed in software coding alone. We then report on the studies that were conducted to investigate the impact of emotions on the productivity of developers. Some studies performed sentiment analysis on text, while others relied on biometric sensors to perform measurements. Most studies, however, relied on self-assessment to obtain data. Overall, the limited number of studies and the inconsistencies in the findings suggest the need for more effective ways to detect users' emotions and related productivity during software development activities.